Improving Customer Satisfaction: Implementing Decentralised Inpatient Discharges At Ward Level - A. R., Abdul Aziz; M. B., Nishazini; Noor Azlinna, Azizan (IOSR, 2013)
Before January 2009, inpatient discharges were done through central discharges system at the ground floor of finance department. Effective January 2010 a new decentralise inpatient discharges system at wad level was implemented . Before the implementation of the new system, data were collected from July 2009 to December 2009 on the total number of feedback form received, number of complaint on hassle of discharge and complaint of long waiting time. After the implementation of the new system, the same data were collected from January to June 2010. The two set of data were compared to see the impact of the new discharge system. Further monitoring was done by collecting data for the first six month of 2011 and the first six month of 2012.Based on the data collected it was found that for a period of July to December 2009, 295 complaints on hassle of discharges and 46 complaints on long waiting time. For the period from January to June 2010, there was no complaint on the hassle of discharges but 38 complaints on the long waiting time. Further monitoring was done from January to June 2011 and it was found that there was no complaint on the hassle of discharges but complaints on the long waiting time had reduced to 8 cases. For the period from January to June 2012, there was no complaint about the hassle but only 6 cases on the long waiting time. Revenue of the hospital grows by 35% from year 2009 to 2012 and PBT grows by 250% from year 2009 to 2012.